Transportation infrastructure and resource allocation of capital market: evidence from high-speed rail opening and company going public. Issue 2 (2nd April 2020) - Jin, Zhi; Zhang, Liguang; Xin, Qingquan
ABSTRACT: Using the high-speed rail opening of each city in China as a natural experiment, we apply the difference-in-differences model to investigate how the transportation infrastructure in a region affects the behaviour of local company going public. We find that after high-speed rail runs through a city, the number of local company going public increases significantly, and the approval probability of going public is improved significantly. Further mechanism analysis shows that the high-speed rail opening reduces the cost of obtaining private information about local companies, making it easier for them to absorb venture capital and hire high-quality intermediary institutions. In addition, the decline of information cost both enables external stakeholders to select better companies and lowers the financing cost of these companies. This paper shows that the improvement of transportation infrastructure can improve corporate financing efficiency and optimise the efficiency of resource allocation in capital markets.